RELIABILITY OF AMYLOID DETECTION IMMUNOASSAY KITS FOR ALZHEIMERS DISEASE SCREENING: A PRELIMINARY STUDY - Putri, Indah Aprianti; Ningrum, Emilna Mega; Noviana, Rachmitasari; Mariya, Silmi; Saepuloh, Uus; Retnani, Elok Budi; Hamdan, Muhammad; Nugraha, Jusak; Darusman, Huda Shalahudin (Jurnal Kedokteran Hewan, 2024)
Alzheimers Disease is a progressive neurodegenerative disease that damages the brain and is part of dementia. Alzheimers dementia is caused by various factors that until now the proper therapy is uncertain. Kit production as a diagnostic tool to support the development of screening for Alzheimers disease is a strategic effort. Screening based on detection with Enzyme-Linked Immunosorbent Assay (ELISA) can work effectively and accurately to optimize a specific antibody material or monoclonal antibody to the A42 peptide. This study aimed to research the reliability of the amyloid detection kit which was developed as an alternative screening test for Alzheimers disease compared to commercially available kits. Based on the results and interpretation of inter and intra-assay coefficients, the in-house ELISA kit has comparable A42 detection to the commercially available ELISA kit